Interval patterns are dependent on metrical position in jazz solos. (June 2023) - Cross, Peter; Goldman, Andrew
During jazz improvisation, performers employ short recurrent musical motifs called licks. Past research has focused on the pitch, intervallic, and rhythmic characteristics of licks, but less attention has been paid to whether they tend to start in the same place within the measure ( metrical dependence ). Licks might be metrically dependent, and where a given lick starts in a measure ( metrical position ) may thus be part of the performer's mental representation of that lick. Here we report the use of a corpus study to investigate whether licks are metrically dependent. We analyzed a subset of solos, all those in 4/4 time ( n = 435), from the Weimar Jazz Database (WJD; Pfleiderer et al., 2017). Using a sliding window technique, we identified melodic sequences ( interval n-grams ) between 3 and 10 intervals in length. We counted the number of times each interval n-gram occurred, and noted the metrical position of the initial note of each occurrence, using different levels of quantization (8th and 16th note). We compared the entropy of the distribution of metrical positions for each n-gram—with lower values indicating a stronger metrical dependence—against simulated counterparts that assumed no relationship between an n-gram and its metrical position (no metrical dependence). Overall, we found that shorter n-grams were metrically dependent, with varying results for longer n-grams. We suggest two possible explanations: either mental representations of licks may encode their metrical features or the metrical position may make certain licks more accessible to the performer. On the basis of our findings we discuss future studies that could employ our methods.